2019
DOI: 10.3390/s19030578
|View full text |Cite
|
Sign up to set email alerts
|

System for Face Recognition under Different Facial Expressions Using a New Associative Hybrid Model Amαβ-KNN for People with Visual Impairment or Prosopagnosia

Abstract: Face recognition is a natural skill that a child performs from the first days of life; unfortunately, there are people with visual or neurological problems that prevent the individual from performing the process visually. This work describes a system that integrates Artificial Intelligence which learns the face of the people with whom the user interacts daily. During the study we propose a new hybrid model of Alpha-Beta Associative memories (Amαβ) with Correlation Matrix (CM) and K-Nearest Neighbors (KNN), whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…After obtaining results of the RSS and SS between neutral mode and each expression for 36 subjects, the results showed that the following FEs; happy, sadness, surprise, anger, disgust, and fear showed a lower SS compared to neutral mode. The highest dissimilar FE was achieved by the disgust expression of 92.01%, which was also agreed with results of Azimi [36] and Márquez-Olivera [37]. While the lowest one achieved by sad expression 93.94%, which is contrary to what has been reported in [37] where it was the happy expression.…”
Section: All Expressions Vs Neutral Modesupporting
confidence: 89%
See 4 more Smart Citations
“…After obtaining results of the RSS and SS between neutral mode and each expression for 36 subjects, the results showed that the following FEs; happy, sadness, surprise, anger, disgust, and fear showed a lower SS compared to neutral mode. The highest dissimilar FE was achieved by the disgust expression of 92.01%, which was also agreed with results of Azimi [36] and Márquez-Olivera [37]. While the lowest one achieved by sad expression 93.94%, which is contrary to what has been reported in [37] where it was the happy expression.…”
Section: All Expressions Vs Neutral Modesupporting
confidence: 89%
“…The highest dissimilar FE was achieved by the disgust expression of 92.01%, which was also agreed with results of Azimi [36] and Márquez-Olivera [37]. While the lowest one achieved by sad expression 93.94%, which is contrary to what has been reported in [37] where it was the happy expression. The following expressions: fear, surprise, anger, happy achieved 93.34%, 92.66%, 92.50%, 92.40% respectively, as shown in Table 10 and Figure 21.…”
Section: All Expressions Vs Neutral Modesupporting
confidence: 89%
See 3 more Smart Citations